Universal Religious Values in Religious Moderation - Siti Ariani; Kukuh Zainul Rahman; Humamurrizqi; M. Sefa Ramdhani (International Journal of Sociology of Religion, 2025)
This article discusses the role of universal religious values in supporting religious moderation as an effort to create harmony and tolerance among religious communities. Universal values such as compassion, justice, peace, fairness, religious freedom, respect, unity, welfare, moderation, balance, tathawur wa ibtikar (moderation and innovation), are able to balance the situation of the people amid differences and conflicts. Using a literature review method from relevant journals, this article highlights how the application of these values can reduce extremism and religious conflict, as well as strengthen social cohesion in a pluralistic society. The results of the study show that religious moderation rooted in universal religious values can be an effective solution in facing the challenges of pluralism and contemporary social dynamics.